1986
DOI: 10.1289/ehp.8670195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phthalic acid esters on the liver and thyroid.

Abstract: The effects, over periods from 3 days to 9 months of administration, of diets containing di-2-ethylhexyl phthalate are very similar to those observed in rats administered diets containing hypolipidemic drugs such as clofibrate. Changes occur in a characteristic order commencing with alterations in the distribution of lipid within the liver, quickly followed by proliferation of hepatic peroxisomes and induction of the specialized P450 isoenzyme(s) catalyzing w oxidation of fatty acids. There follows a phase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 79 publications
(73 reference statements)
7
54
0
Order By: Relevance
“…When T 4 was administered to thyroidectomized rats, the increases in the hormone levels and in the number of developed follicles were suppressed at levels equating those of intact rats. Circulating levels of thyroid hormone were obviously low in the rats receiving DEHP 13,14) , and in our present study, the serum T 4 level was significantly lowered by treatment with 2,000 mg DEHP (P<0.05) in intact rats, whereas the T 4 level tended to be decreased by 2,000 mg DEHP in hypox rats, although the decrease was without statistical significance (Fig. 1).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…When T 4 was administered to thyroidectomized rats, the increases in the hormone levels and in the number of developed follicles were suppressed at levels equating those of intact rats. Circulating levels of thyroid hormone were obviously low in the rats receiving DEHP 13,14) , and in our present study, the serum T 4 level was significantly lowered by treatment with 2,000 mg DEHP (P<0.05) in intact rats, whereas the T 4 level tended to be decreased by 2,000 mg DEHP in hypox rats, although the decrease was without statistical significance (Fig. 1).…”
Section: Discussionsupporting
confidence: 48%
“…DEHP is also known to suppress enzyme activity in the liver of rats 13,14) . When fed with diets containing DEHP, the serum thyroxine (T 4 ) levels declined to about half of those of control rats 3 d after the initiation of intake of DEHP in diet 13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.intechopen.com Rodent studies found histopathological changes in the rat thyroid glands after exposure to di(2-ethylhexyl) phthalate (DEHP), di-noctyl phthalate (DnOP) and di-n-hexyl phthalate (DnHP), corresponding to thyroid hyperactivity (Hinton et al, 1986;Howarth et al, 2001;Mitchell et al, 1985;Poon et al, 1997;Price et al, 1988). Long-term treatment with high doses of DEHP resulted in basophilic deposits in the colloid and enlargement of the lysosomes (Mitchell et al, 1985).…”
Section: Phthalatesmentioning
confidence: 99%
“…Wenzel et al 134) found that DEHP and other phthalates enhance iodine uptake in rat thyroid follicular cells. In rats fed DEHP-contaminated diets, histological changes in the thyroid and a decrease in plasma T 4 were seen, but T 3 level remained unchanged, [135][136][137][138] while rats intravenously receiving DEHP showed increased concentrations of serum T 4 and T 3 . 139) Exposure of male rats to DBP by oral gavage also caused a reduction in T 4 and T 3 levels in a dose-dependent manner.…”
Section: Phthalatesmentioning
confidence: 99%